Expanded Choreographies - Choreographic Histories Trans-Historical Perspectives Beyond Dance and Human Bodies in Motion - Leon, Anna (TanzScripte, 2022)
From objects to sounds, choreography is expanding beyond dance and human bodies in motion. This book offers one of the rare systematic investigations of expanded choreography as it develops in contemporaneity, and is the first to consider expanded choreography from a trans-historical perspective. Through case studies on different periods of European dance history - ranging from Renaissance dance to William Forsythe's choreographic objects and from Baroque court ballets to digital choreographies - it traces a journey of choreography as a practice transcending its sole association with dancing, moving, human bodies.